Family history, near work, outdoor activity, and myopia in Singapore Chinese preschool children. Issue 8 (14th May 2010) - Low, Wilson; Dirani, Mohamed; Gazzard, Gus; Chan, Yiong-Huak; Zhou, Hui-Jun; Selvaraj, Prabakaran; Au Eong, Kah-Guan; Young, Terri L; Mitchell, Paul; Wong, Tien-Yin; Saw, Seang-Mei
Abstract : Aims: To investigate the risk factors for myopia, including near work and outdoor activity, in Singapore Chinese preschool children. Methods: A cross-sectional study, with disproportionate random sampling by 6-month age groups, of 3009 Singapore Chinese children aged 6–72 months was performed. Information on family history, near work and outdoor activity was obtained. Spherical equivalent refraction (SER) was assessed. Results: Children with two myopic parents were more likely to be myopic (adjusted OR=1.91; 95% CI 1.38 to 2.63) and to have a more myopic SER (regression coefficient=−0.35; 95% CI −0.47 to −0.22) than children without myopic parents. For each 1 cm taller height, the SER was more myopic by 0.01 dioptres. Neither near work nor outdoor activity was associated with preschool myopia. Conclusions: A family history of myopia was the strongest factor associated with preschool myopia. In contrast, neither near work nor outdoor activity was found to be associated with early myopia. These data suggest that genetic factors may play a more substantial role in the development of early-onset myopia than key environmental factors.